Biochemical and genetic analysis of the Mycobacterium smegmatis CnoX Chaperedoxin - Watkins, Ariana Heloise Jo (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Mycobacterium (M.) tuberculosis (Mtb) encounters numerous physical and chemical stresses associated with host immunity during infection. These include exposure to reactive oxygen, chlorine and nitrogen species, low pH, hypoxia, nutrient starvation, and metal toxicity. Cellular proteins are particularly susceptible to damage by these stresses, and the ability to prevent their irreversible damage is consequently crucial for bacterial growth and survival. Mtb employs a network of proteins that includes chaperones, disaggregases, and proteases to maintain the integrity of its proteome. The chaperedoxin, CnoX, is a recently identified stress-inducible chaperone that combines redox and holdase activities to prevent the over-oxidation and aggregation of proteins in E. coli and other proteobacterial species. In this study, we identified orthologs of the E. coli CnoX (EcCnoX) in Mtb and M. smegmatis (Msm). Bioinformatics analysis of the Mtb and Msm CnoX orthologs (MtCnoX and MsCnoX, respectively) revealed that they possess similar domains, domain architectures and predicted tertiary structures as previously characterised CnoX enzymes, i.e. an N-terminal thioredoxin (Trx) domain fused to a C-terminal TPR-motif containing domain. The EcCnoX, MsCnoX, and MtCnoX enzymes were expressed as recombinant, His-tagged proteins in E. coli and purified to near homogeneity. Biochemical analysis of the recombinant CnoX enzymes revealed that the MsCnoX and MtCnoX both lack thiol-disulphide oxidoreductase (thioredoxin) activity, as evidenced by their inability to catalyse the reduction of the disulphide bonds of insulin in vitro. Both mycobacterial CnoX enzymes displayed activity as chaperones (holdases) during thermal aggregation assays of the model substrate, malate dehydrogenase (MDH). In contrast to previously reported findings for EcCnoX, the holdase activity of the mycobacterial CnoX enzymes was constitutive and did not require exposure to hypochlorous acid (HOCl) for activation. To establish the physiological role of CnoX in Msm, cnoX knockdown (KD) and knockout (KO) mutants were generated using CRISPRi-mediated gene silencing or homologous recombination, respectively. Consistent with previous findings, CnoX activity was not essential for the growth of Msm under conventional growth conditions. Reducing or eliminating CnoX activity in the Msm KD or KO mutants, respectively, did not confer increased sensitivity to HOCl as has been observed for an E. coli ï „cnoX mutant. Reduced CnoX activity in Msm did, however, confer sensitivity to the superoxide generator, plumbagin, and front-line antitubercular drugs rifampicin and isoniazid. The combination of biochemical and physiological data presented suggests that MsCnoX may function as a holdase for substrates following proteotoxic damage induced by certain types of oxidants, a line of investigation that will be pursued in future studies.
Keywords: Mycobacterium smegmatis; Mycobacteria; ENOX1; Proteostasis; Molecular chaperones; Heat shock proteins; Oxidation-reduction reaction; Redox